India’s Arctic Policy: a critical appraisal - Pareek, Nikhil; Pareek, Nisha (Polar Research Institute of China - PRIC, 2022)
After much procrastination, the Indian government has released its much awaited and delayed Arctic Policy document on 17 March 22 with the theme being “Building a Partnership for Sustainable Development”. It has been 15 years since India commenced its scientific research in the Arctic region and this policy document, charting out the direction that India aspires to assume will be keenly examined by the diverse stakeholders of the region. Despite being an Arctic Council observer for nearly a decade, India continues to view the Arctic from a mere scientific prism and yet again missed on the opportunity to elucidate her geo-economic, geostrategic, economic and geopolitical aspirations in the hugely vital region. There is no gainsaying that the research bases discreetly also act as pillars of geopolitical engagement and indirectly this scientific diplomacy ushers in peace and prevent conflict situations yet a holistic national policy enunciating a roadmap and vision for dealing in a region which has eight sovereign states, thirteen sovereign states as observers, various intergovernmental and inter-parliamentarian outfits, NGOs and a complex governance structure was much awaited.